Efektivitas Penggunaan E-Money Sebagai Alat Transaksi Parkir Elektronik (E-Parkir) di Kota Medan - Imsar Imsar; Muhammad Dimas Prasetya (Universitas 45 Surabaya, 2023)
Parking is one of the activities that is often carried out to save or set aside private vehicles or public transportation. Along with advances in digital or electronic technology, the current parking method has also begun to develop with electronic methods. The process of collecting ordinary parking is considered to often occur due to leakage of citation fees due to a lack of supervision and the large number of illegal fees, for this reason parking using the electronic method is considered capable of overcoming the problems that occur in the ordinary parking collection system. However, there are several indications or problems that can lead to leakage of fees, such as the lack of participation of the public who make payments using electronic money so that the payment data collection process is not detected. For this reason, the purpose of this study was to determine the effectiveness of using e-money as a means of electronic parking transactions (E-Parking) on ​​Jalan Palangkaraya, Medan. This research is a qualitative research with a descriptive approach and simple quantitative calculations. Research uses data collection techniques with observation, interviews and documentation. The data obtained by this study are through primary data and secondary data. The results of this study indicate that the use of e-money as a means of paying for electronic parking in Medan City is less effective, based on observations made by researchers to the public showing ineffective results where only 53 out of 311 people use e-money to make payments electronic parking.